Pengaruh Pemberian VCO Terhadap Penyembuhan Luka Perineum Pada Ibu Nifas Di Rumah Sakit Ibu Dan Anak Kasih Fatimah Kotamobagu - Sutrisna Pratiwi Simbuang; Enny Yuliaswati (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Background: The postpartum period is a very complex period experienced by a woman, especially for those who have given birth for the first time. The problem that we often encounter in the early postpartum period is the discomfort of mothers breastfeeding their babies because they are bothered by the presence of stitches for mothers who experience perineal lacerations. Objective: to determine the effect of VCO administration on perineal wound healing in postpartum women at Hospital Mother and Child Kasih Fatima Kotamobagu Methods: Quasi experimental design with post-test only with nonequivalent groups with Mann-Whitney test with 34 respondents and divided into 2 groups of cases and controls Results: Based on the statistical test output, it is known that the Asymp Sig (2-tailed) value is 0.000 <0.05, so it can be concluded that the hypothesis is accepted. Thus it can be said that there is an effect of VCO administration on perineal wounds with perineal wound healing. Conclusion: There is an effect of giving VCO with healing perineal wounds in postpartum women at RSIA Kasih Fatimah Kotamobagu, with this research it is hoped that VCO administration can be applied by health workers for wound healing, especially pernieal wounds.